A bead–string Co/C@BNNT nanocomposite: preparation and tunable electromagnetic wave absorption performance. Issue 11 (28th February 2023) - Liu, Lu; Wen, Bianying
Abstract : A bead–string Co/C@BNNT nanocomposite was fabricated by in situ synthesis combined with the carbonization method using the Co-MOF ZIF-67 as the precursor and rigid insulating boron nitride nanotubes (BNNTs) as the carrier. Abstract : A bead–string Co/C@BNNT nanocomposite was fabricated by in situ synthesis combined with the carbonization method using the Co-MOF ZIF-67 as the precursor and rigid insulating boron nitride nanotubes (BNNTs) as the carrier. The internal structure and external morphology of the Co/C@BNNT nanocomposites were characterized, and the electromagnetic wave (EM) absorption properties and mechanism were investigated. According to the findings, Co/C granules were evenly distributed on BNNTs and a stable bead–string morphology was maintained. Such a unique rigid bead–string structure not only provides multiple interfaces and a mesoporous structure but also facilitates building of a 3D conductive network in the matrix. Besides, the good impedance matching benefit of insulating BNNTs also helps to improve the EM wave absorption. The carbonization temperature can effectively affect the size of internally reduced Co particles in Co/C beads and the electrical conductivity of the Co/C@BNNT nanocomposites. The EM wave absorption test results indicate that the Co/C@BNNT-800/paraffin (30 w/70 w) sample has the best absorption capability, it achieves a minimum reflection loss (RL) of −71.7 dB at a matching thickness of 2.42 mm. Moreover, its effective absorption bandwidth (EAB) reaches 3.29 GHz, covering 78.3% of the X-band test frequency, which is considerably better than the Co/C granules/paraffin (−7.5 dB) at the same filler ratio. The excellent EM wave absorption capability is contributed by a collaborative energy loss mechanism, including multi-interface polarization loss, conduction loss, dielectric loss and magnetic loss. The innovative bead–string Co/C@BNNT nanocomposites provide a reference for designing powerful MOF-derived carbon-based microwave absorbing materials.